Single nucleotide polymorphisms in the myostatin (MSTN) and muscle creatine kinase (CKM) genes are not associated with elite endurance performance - Döring, F.; Onur, S.; Kürbitz, C.; Boulay, M. R.; Perusse, L.; Rankinen, T.; Rauramaa, R.; Wolfarth, B.; Bouchard, C. (Scandinavian Journal of Medicine & Science in Sports, 2011)
Maximal oxygen uptake (VO2max) is one of the most important determinants of elite endurance performance. VO2max is determined by a whole range of genetic and environmental factors. Single nucleotide polymorphisms (SNPs) in muscle myostatin (MSTN) and creatine kinase (CKM) genes are candidates for VO2max and skeletal muscle performance phenotypes. Common MSTN (rs3791783, rs11681628 and rs7570532) and CKM (rs344816, rs10410448, rs432979, rs1133190, rs7260359, rs7260463 and rs4884) SNPs, selected from HapMap CEU data in order to tag the genetic variability of the proteins, were genotyped in 316 male Caucasian elite endurance athletes and 304 sedentary controls from the Genathlete study. Association with elite endurance performance was determined by logistic regression analysis. The P-value for statistical significance was set at <0.01. None of the SNPs or haplotypes showed a significant association with elite endurance status. We conclude that common variants of MSTN and CKM genes do not play a role in attaining high-level endurance performance in Caucasian populations.